KARAKTERISTIK MARSHALL CAMPURAN ASPAL KARET AC-WC YANG MENGGUNAKAN KARET ALAM DAN LIMBAH BAN BEKAS SEBAGAI BAHAN SUBSTITUSI PASIR - Jimmyanto, Hendrik; Ramadhani, Ramadhani; Aminuddin, Kiagus Muhammad (TEKNIKA: Jurnal Teknik, 2025)
The increasing number of vehicles each year causes a high traffic load, which can lead to damage to the roads. The pavement plays an important role in distributing the load of vehicles to the soil beneath it and in reducing soil stress. Sustainable road construction can be achieved by optimizing resource utilization and using alternatives to waste, such as waste rubber from scrap tires and natural rubber. The purpose of this study is to analyze the optimal asphalt content of a mixture that uses solid natural rubber and waste tires as substitute fine aggregates in Asphalt Concrete – Wearing Course. The experiment involved testing the characteristics of asphalt and conducting Marshall tests. Subsequently, the optimal asphalt binder content (OAC) of each proposed mixture was determined based on the results of the Marshall test. The percentage of fine aggregate substitution was 0%, 25%, and 50% of the weight of river sand. The results of the Marshall test showed that substituting fine aggregate with natural rubber and waste tires affected the physical parameters and performance of the mixture, specifically stability and flow. The range of OAC obtained indicated that the use of rubber asphalt and the substitution of river sand had a significant impact on the physical characteristics of the asphalt mixture, where higher concentrations of rubber asphalt contributed to an increase in OAC. This finding indicates the potential for using rubber asphalt to improve the performance of the mixture in road construction. Keywords: Asphalt concrete – wearing course, Waste tire, Solid natural rubber, Marshall, Optimal asphalt binder content